Influences of Age, Gender, and Circadian Rhythm on Deceleration Capacity in Subjects without Evident Heart Diseases. Issue 2 (12th August 2014) - Zhao, Ruifu; Li, Dan; Zuo, Ping; Bai, Rong; Zhou, Qiang; Fan, Jingjing; Li, Chengpeng; Wang, Lin; Yang, Xiaoyun
<x xml:space="preserve">Abstract</x> Background Deceleration capacity (DC) is a newly found predictor of mortality after myocardial infarction. Age‐, gender‐, and circadian rhythm–related differences in DC may limit its predictive value, which should be considered in clinical settings. Methods DC, average heart rate, and HRV parameters, including 24 hours, awaking state (15:00–20:00) and sleeping mode (00:00–05:00) strips from 24 hours Holter recordings in 636 subjects without heart diseases were examined. Heart rate variability was analyzed in time domains (standard deviation of all normal‐to‐normal intervals [SDNN], normal‐to‐normal RR intervals in all 5‐minute segments [SDANN], and root mean square successive difference [RMSSD]). Results The DC, SDNN, SDANN, RMSSD, and heart rate decreased with age. Deceleration capacity was significantly lower in patients greater than 50 years of age. The largest decrease of SDNN, SDANN, and RMSSD occurred in patients 30–39 years of age. The values of SDNN, SDANN, and DC of women were lower than that of men in the young and middle‐aged groups, but age‐related decrease of DC in men was greater than that in women. Heart rate of women was significantly higher than that of men in younger subjects, especially in a sleeping mode. There were higher values of DC and RMSSD during sleeping than that during a waking state. Conclusions The age, gender, and circadian rhythm may be useful when evaluating cardiac autonomic function and need to be considered when evaluating DC and HRV in clinical and scientific researches.